2016
DOI: 10.1126/scisignal.aac8035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small-molecule ligand that activates the neuropeptide receptor GPR171 and increases food intake

Abstract: Several neuropeptide systems in the hypothalamus, including neuropeptide Y and agouti-related protein (AgRP), control food intake. Peptides derived from proSAAS, a precursor implicated in the regulation of body weight, also control food intake. GPR171 is a heterotrimeric guanine nucleotide–binding protein (G protein)– coupled receptor (GPCR) for BigLEN (b-LEN), a peptide derived from proSAAS. To facilitate studies exploring the physiological role of GPR171, we sought to identify small-molecule ligands for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
3
34
1
Order By: Relevance
“…Moreover, ProSAAS-derived peptides were also shown to colocalize with the feeding-regulatory peptide NPY in the mouse HT, and were concentrated in the arcuate nucleus (37). Because the receptors for several ProSAAS-derived peptides such as big LEN and PEN have been identified (50,51), a small-molecule ligand of GPR171, a hypothalamic G proteincoupled receptor for Big LEN, was screened and demonstrated to increase food intake in mice through the activation of GPR171 (52). Taken together, these studies suggested the potential function of ProSAAS peptides as regulators of food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ProSAAS-derived peptides were also shown to colocalize with the feeding-regulatory peptide NPY in the mouse HT, and were concentrated in the arcuate nucleus (37). Because the receptors for several ProSAAS-derived peptides such as big LEN and PEN have been identified (50,51), a small-molecule ligand of GPR171, a hypothalamic G proteincoupled receptor for Big LEN, was screened and demonstrated to increase food intake in mice through the activation of GPR171 (52). Taken together, these studies suggested the potential function of ProSAAS peptides as regulators of food intake.…”
Section: Discussionmentioning
confidence: 99%
“…One GPR68 PAM, ogerin, was demonstrated to have on-target activity in vivo by modulating conditioned fear responses in mice. A similar approach has recently been used to identify small molecule ligands for the oGPCRs GPR171 (Wardman et al, 2016) and MRGPRX2 (Lansu et al, 2017), and these compounds were subsequently used to further characterize the receptor’s role in feeding behavior and itch, respectively.…”
Section: Exploiting Gpcr-ligand Structures For Drug Discoverymentioning
confidence: 99%
“…A docking screen of 10,526 in-house compounds against a homology model of GPR171 (ref. 61) identified a dicarboxyphenyl vinyl amide, MS0015203 (ZINC4956098; MW 249), as an orthosteric agonist 61 . MS0015203 had activity in vivo in modulating feeding, which is unusual for a primary fragment hit.…”
Section: New Chemistry For New Targetsmentioning
confidence: 99%